WAYS TO DEVELOP THE SPEECH OF CHILDREN WITH DISABILITIES USING FAIRY TALE THERAPY - Musayeva Nargiza Sayfullayevna (Web of Journals Publishing, 2025)
This article provides information about children with disabilities, the characteristics of their speech disorders, as well as effective methods of using art therapeutic technologies to eliminate speech disorders.
Keywords: Art therapy, fairy tale therapy, expressive speech, affective speech, psychotherapy, psychocorrection, dyspraxia, dramatization, disabled children, speech disorders.